2016
DOI: 10.1074/jbc.m116.734020
|View full text |Cite
|
Sign up to set email alerts
|

The Coronary Artery Disease-associated Coding Variant in Zinc Finger C3HC-type Containing 1 (ZC3HC1) Affects Cell Cycle Regulation

Abstract: Genome-wide association studies have to date identified multiple coronary artery disease (CAD)-associated loci; however, for most of these loci the mechanism by which they affect CAD risk is unclear. The CAD-associated locus 7q32.2 is unusual in that the lead variant, rs11556924, is not in strong linkage disequilibrium with any other variant and introduces a coding change in ZC3HC1, which encodes NIPA. In this study, we show that rs11556924 polymorphism is associated with lower regulatory phosphorylation of NI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 47 publications
2
18
0
Order By: Relevance
“…Together with the recently published report of Jones et al, 22 this study strengthens the link between ZC3HC1 and CAD and form the basis for follow-up experiments to be performed in the context of models of atherosclerosis. This could be achieved by establishing stable isogenic CAD-relevant cell lines specifically edited for R363H (eg, via CRISPR/Cas9), but ultimately experiments involving whole animals will be required.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Together with the recently published report of Jones et al, 22 this study strengthens the link between ZC3HC1 and CAD and form the basis for follow-up experiments to be performed in the context of models of atherosclerosis. This could be achieved by establishing stable isogenic CAD-relevant cell lines specifically edited for R363H (eg, via CRISPR/Cas9), but ultimately experiments involving whole animals will be required.…”
Section: Discussionmentioning
confidence: 78%
“…Although this article was in revision, work by Jones et al 22 reinforcing the interaction between CCNB1 and rs11556924 was published. Using isogenic adenocarcinoma cell lines, the authors demonstrate that the risk allele is associated with a slower CCNB1 nuclear accumulation, increased total CCNB1, as well as a higher mitotic index, although, unexpectedly, without proliferation changes.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in the course of our experiments, initially all performed with cells in which ZC3HC1 had been knocked down by RNAi, we had realised that this protein was most likely neither essential for cell cycle progression nor cellular housekeeping activities in interphase (Figure S14). However, even though these early results turned out to be in accordance with the finding that mice in which the ZC3HC1 gene had been knocked out by homologous recombination are viable [104,105], the alleged role for ZC3HC1 in regulating cell cycle progression via controlling cellular levels of CCNB1 was recurrently reported to manifest itself in a range of aneuploid human tumour cell lines and other types of immortalised human cells [104,[106][107][108]. HeLa cells were actually suggested to be amongst those cells in which such ZC3HC1 knockdown phenotypes were most pronounced [104], ranging from most cells of a ZC3HC1-deficient HeLa population being no longer capable of cell cycle progression and entering apoptosis instead [104], to hyperproliferation of another ZC3HC1-deficient HeLa population and conspicuous increase in its cell numbers [108], when using the one or other ZC3HC1 siRNA.…”
Section: Zc3hc1 Is Not Required For Cellular Housekeeping Activities In Human Tumour and Non-tumour Cell Lines Of Ectodermal Mesodermal Amentioning
confidence: 68%
“…In the locus #23, we found the strongest evidence for the gene ZC3HC1 (Supplementary Table S4). ZC3HC1 contains a functional missense polymorphism rs11556924 59 , which is the lead SNP tagging this locus. However, our SMR/HEIDI analysis revealed that either rs11556924 or other SNP in LD with rs11556924 is simultaneously associated with CAD and the KLHDC10 gene expression in blood (Supplementary Table S2).…”
Section: Rs867186 20: 33 764 554 Procr Mmp24-as1-edem2mentioning
confidence: 99%